Participación del proceso de exclusión de AMPc a través del transportador MRP4 en la capacitación espermática en mamíferos - Alonso, Carlos Agustín Isidro (2018)
To fertilize the oocyte, mammalian spermatozoa must undergo a series of biochemical changes known as capacitation. Activation of PKA is essential for capacitation to take place, and cAMP levels are tightly regulated during this process. Traditionally, cAMP levels are determined by the ratio between its synthesis and degradation. However, we recently described that cAMP efflux system through the Multidrug Resistance Protein 4 (ABCC4/MRP4) contributes to modulate the availability of this nucleotide, while provides cAMP to the extracellular space for further signalling events in bovine cryopreserved sperm.\nIn the present study, our aim was to deepen the role of cAMP/MRP4 efflux system in mammalian sperm capacitation.\nAltogether, our results suggest that MRP4 plays a critical role in sperm capacitation in bovine, mouse and human. However, the mechanisms associated with cAMP efflux are different between mouse and bovine spermatozoa. While in the latter, cAMP efflux primarily provides for further extracellular purinergic signaling through A1, in the former cAMP efflux regulates PKA-Ca2+ axis. In this context, cAMP efflux system emerges as an important player in sperm physiology and thus become an attractive novel target for designing novel contraceptive drugs.